The Role of the School Literacy Program in Increasing Students' Interest in Reading in Islamic Religious Learning at Muhammadiyah 1 South Sangatta Elementary School - Aulia Sari; Anjani Putri Belawati Pandiangan; Moh. Tauhid (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
The purpose of this study was to determine the role of the school literacy program in increasing students' interest in reading in Islamic religious education learning at SD Muhammadiyah 1 Sangatta Selatan. The type of research that the author uses in this research is field research using a qualitative research approach. In collecting data, the author uses data collection techniques, namely observation, interviews, and documentation with descriptive techniques. Based on the results of the study, it can be concluded that the literacy program plays an important role in increasing students' interest in reading, insight, and learning independence, as well as helping to understand Islamic teachings. However, its implementation is constrained by the influence of gadgets, low parental motivation, limited vocabulary, and lack of facilities such as libraries and books at home.